Emotionality and pleasantness of mixed‐emotion stimuli: The role of language, modality, and emotional intelligence. (28th January 2020) - Mavrou, Irini; Dewaele, Jean‐Marc
Abstract : The study aimed to explore how 174 Spanish first language (L1) and foreign language (LX) users perceive emotionality and pleasantness in audiovisual and purely visual material eliciting blended emotions, and whether cultural background and Trait Emotional Intelligence (EI) are linked to emotion perception. Overall, LX users tended to provide higher ratings of emotionality and pleasantness than L1 users, suggesting that they might be aware of the LX detachment effect and overcompensate when providing emotion perception ratings. American participants rated the stimuli as more emotional and pleasant than Asian participants regardless of modality of presentation. On the other hand, Trait EI turned out to be unrelated to emotionality and pleasantness contrary to previous evidence suggesting a positive role of EI in decoding emotions. Abstract : El estudio persiguió explorar cómo 174 usuarios de español como primera lengua (L1) y lengua extranjera (LX) perciben la emocionalidad y el agrado en material audiovisual y puramente visual inductor de emociones mixtas, y si los antecedentes culturales y el rasgo inteligencia emocional (IE) están vinculados a la percepción emocional. En líneas generales, los usuarios de LX tendieron a proporcionar valores más altos de emocionalidad y agrado que los usuarios de L1, lo que sugiere que podrían ser conscientes del efecto de distanciamiento emocional en relación con la LX y sobrecompensar al proporcionar valores de percepción emocional. Los participantes estadounidenses valoraron los estímulos como más emocionales y agradables que los participantes asiáticos, independientemente de la modalidad de presentación de esos estímulos. Por otro lado, el rasgo IE no se asoció con los valores de emocionalidad y agrado, resultado que contradice la evidencia empírica previa sobre el papel positivo de la IE en la decodificación de emociones.